PENDEKATAN ANALISIS BIPLOT DALAM MENDESKRIPSIKAN POSISI RELATIF ANTAR SMA DI KOTA DENPASAR - MELISSA, MELISSA (E-Jurnal Matematika; Volume 1, No 1, Tahun 2012, 2012)
Education is one of the important aspect of society life which have served to increase the quality of life. School is one place to obtain formal education. Currently, there are many schools in the city of Denpasar as the increasing number of students compared with the past. Various advantages and strengths of these schools are often used as a material consideration by parents whose children will continue their school to senior high school level. The information regarding the comparison between schools will be able to assist parents in choosing schools for their children. This study aims to analyze the relative posisition among senior high school in Denpasar, especially among state high school and private high school. Based on the analysis of biplot using eleven variables . The analysis results obtained five groups of objects with specific variables within each group.
Keywords: biplot; posisi relatif; pendidikan